Liquid biopsy in biliary tract cancer from blood and bile samples: current knowledge and future perspectives - Gianluca Arrichiello; Valeria Nacca; Fernando Paragliola; Emilio Francesco Giunta (Open Exploration Publishing Inc., 2022)
Biliary tract cancer (BTC) is an aggressive tumor characterized by a poor prognosis. In the latest years, targetable genetic alterations have been discovered in BTC patients, leading to the approval of new targeted therapies. Liquid biopsy, which is a non-invasive method for detecting tumor biomarkers from fluid samples, is a useful tool for diagnosis and molecular characterization, but also for prognosis assessment and monitoring of treatment response. In this review, recent works on liquid biopsy in BTC patients were analyzed, focusing on some relevant aspects for clinical use and trying to depict the future role of this technique. Moreover, differences between plasma and bile samples were pointed out, in light of the peculiar biology of BTC and the possibility of using bile as an alternative source of cell-free DNA (cfDNA) for genomic analysis. In the era of precision oncology, the increasing adoption of liquid biopsy in BTC patients will certainly improve the management of this disease.